Inulinases produzidas por leveduras isoladas do semiárido baiano: estudos de imobilização e aplicação na produção de frutose e fruto-oligossacarídeos - Ribeiro, Geise Camila de Araujo (2014)
The exploration of the microorganisms species semiarid region has become a viable alternative for the industry, especially producing yeast inulinases which can be applied in the production of fructo-oligosaccharides and fructose from the hydrolysis of inulin. This work had as its theme the study of the immobilization inulinases enzymes produced by yeasts of the semiarid region of Bahia, with the overall objective of the work is to study the application of inulinases immobilized in the production of concentrated fructose and fructo-oligosaccharides. The strains of yeast Pseudozyma sp. (CCMB 306) and Rhodotorula mucilaginosa (CCMB 604) were obtained from the Culture Collection of Microorganisms of Bahia (CCMB), Universidade Estadual de Feira de Santana (UEFS). Immobilization was performed using as support eggshell, celite, Immobeads®, Sepabeads® and silica, and the results analyzed using the Origin version 8.5.1 program. Immobilization in solid supports inulinase shown to be a viable technique, since the non-inactivated enzyme, showing increased activity in the inulinase CCMB 306 samples immobilized on celite in organic medium. Optimization of fructo-oligosaccharides production was achieved the highest concentration of product in samples with inulin concentration of 25% and time of reaction 16 h. In conclusion, the application of inulinases enzymes produced by micro-organisms of the semiarid in the hydrolysis of inulin is of significant importance for biotechnology development in the region.